Planning beyond the metro: Rural travel behavior and the built environment - Harry Schukei; Dana Rowangould (Journal of Transport and Land Use)
Reducing greenhouse gas (GHG) emissions from transportation is particularly challenging in rural communities. People living in rural areas are more vehicle reliant and are also more likely to face barriers to meeting their mobility needs. One approach to reducing vehicle travel without exacerbating mobility challenges is through directing population growth into compact multimodal communities. Despite substantial differences in travel in rural versus urban contexts, very little prior research has evaluated the relationship between travel and the built environment (BE) in rural areas. We use spatially detailed travel behavior data to evaluate the relationships between BE factors and sustainable travel behaviors in rural communities in the United States. We find that the relationship between travel and the BE differs between rural and urban areas, with local access exhibiting a weaker association with travel behavior in rural communities when compared with urban communities. Conversely, regional access exhibits a larger association with travel behavior in rural communities. We also found that the association between personal characteristics and travel behavior was significantly smaller in rural communities. Furthermore, our results suggest that the relationships between travel and the BE may differ across different types of rural communities.